Role Of Floating Microspheres in The Drug Delievery System - Kaur, Harpreet; Negi, Anjali (Journal of Neonatal Surgery, 2025)
In latest years of, drug delivering system has made significant advancements to enhance the effectiveness and safety of medications. Among these, oral drug delivery stands out as a popular choice for administering treatments because of its convenience, patient-friendly nature, and cost-effectiveness.1 Focused medication transport approaches exemplify an additional inventive strategy designed to transport medications to precise locations within the organism, thereby reducing overall exposure and related adverse effects. By targeting drugs to tissues or organs, these improve treatment effectiveness while minimizing overall drug doses required. Despite their potential benefits,targeted delivery systems necessitate sophisticated design and manufacturing techniques, limiting their applicability to certain drugs and therapeutic indications.